2016
DOI: 10.1097/qai.0000000000001149
|View full text |Cite
|
Sign up to set email alerts
|

Plasma n-6 Fatty Acid Levels Are Associated With CD4 Cell Counts, Hospitalization, and Mortality in HIV-Infected Patients

Abstract: Background Fatty-acids, including n6 series, modulate immune function but their effect on CD4 cell counts, death or hospitalization in HIV-infected patients on antiretroviral therapy is unknown. Methods In a randomized trial for effects of multivitamins in HIV-infected patients in Uganda, we used gas chromatography to measure plasma n6-fatty acids at baseline, determined CD4 counts at baseline, 3, 6, 12 and 18 months and recorded hospitalization or death events. The associations of fatty acids with CD4 count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This may explain the associations between lipid plasma levels and Gag-specific response that we have shown in this work. The specific role of each lipid subclasses on immune cells is uncertain and may vary according to lipid subtypes, but new evidence is emerging in the scenario of HIV infection [[66], [67], [68]]. Modulation of fatty acid synthesis and oxidation pathways could be used as strategies to prevent inflammatory T-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the associations between lipid plasma levels and Gag-specific response that we have shown in this work. The specific role of each lipid subclasses on immune cells is uncertain and may vary according to lipid subtypes, but new evidence is emerging in the scenario of HIV infection [[66], [67], [68]]. Modulation of fatty acid synthesis and oxidation pathways could be used as strategies to prevent inflammatory T-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these studies have shown lower plasma levels of LA (C18:2n-6) in HIV-infected patients with advanced disease [ 24 ]. Interestingly, a study in HIV-infected patients in Uganda showed that the risk of death or hospitalization decreased significantly with an increase in LA or GLA levels, and low levels of LA and GLA were associated with low CD4+ T cell counts [ 25 ]. LA is an essential FA because humans cannot synthesize it.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports have focused on abnormalities in plasma levels of FAs in HIV-infected patients treated with protease inhibitors and in patients with lipodystrophy syndrome [ 20 , 21 , 22 , 23 ]. A few studies, however, have shown alterations in FA composition in untreated HIV-infected children and during early HIV infection, potentially contributing to disease progression in individuals [ 24 , 25 , 26 ]. In support of this notion, there is accumulating evidence that FAs play a crucial role in the innate immune responses against various infections such as influenza and tuberculosis [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dihomo-Îł-linolenic acid and arachidonic acid, in particular, are precursors for the synthesis of prostaglandins and eicosanoids, which mediate the effects of type I IFNs during antiviral immune response ( 52 ). It has been previously reported that linoleic acid metabolism positively correlated with CD4 + T cell frequency in HIV-infected patients, whereas its metabolic dysregulation was strongly associated with disease progression and mortality ( 53 ). Finally, RA and bile acid metabolism, known to regulate gut lymphocyte homing and mucosal homeostasis, were significantly boosted in MSC-treated animals.…”
Section: Discussionmentioning
confidence: 99%